CO2 Sequestration and Valorization 2014
DOI: 10.5772/57444
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline and Alkaline-Earth Ceramic Oxides for CO2 Capture, Separation and Subsequent Catalytic Chemical Conversion

Abstract: CO 2 capacity (mmol/g) Ceramic Figure 1. Theoretical CO 2 capture capacities for different alkaline and alkaline-earth ceramics. In the Li 8 SiO 6 (labeled as *) and Li 4 SiO 4 (labeled as +), the maximum capacity can depend on the CO 2 moles captured in each different phase formed (Li 8 SiO 6 + CO 2 → Li 4 SiO 4 + CO 2 → Li 2 SiO 3 + Li 2 CO 3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 175 publications
(264 reference statements)
0
5
0
Order By: Relevance
“…The presence of a supported metal oxide nanocluster on the rutile (110) surface presents potentially active sites for molecular adsorption that are not available on the corresponding surfaces of the alkaline earth oxides or on rutile (110). There has been a high level of interest in studying the interaction of water and CO2 on alkaline earth metal oxide surfaces [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101] . The interaction of water at oxide surfaces is always of interest due to the presence of atmospheric water under many conditions and the possibility of surface hydroxylation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of a supported metal oxide nanocluster on the rutile (110) surface presents potentially active sites for molecular adsorption that are not available on the corresponding surfaces of the alkaline earth oxides or on rutile (110). There has been a high level of interest in studying the interaction of water and CO2 on alkaline earth metal oxide surfaces [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101] . The interaction of water at oxide surfaces is always of interest due to the presence of atmospheric water under many conditions and the possibility of surface hydroxylation.…”
Section: Introductionmentioning
confidence: 99%
“…The capture of CO2 occurs chemically through chemisorption and can produce the corresponding alkaline earth carbonate. These authors showed that MgO and CaO are among the materials with the best CO2 capture properties, with capacities of 17 mmol/g and 25 mmol/g 87 . In an early study, Pacchioni et al 97 studied CO2 adsorption at cluster models of MgO and CaO, using Hartree-Fock and MP2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a supported metal oxide nanocluster on the rutile (110) surface presents potentially active sites for molecular adsorption that are not available on the corresponding surfaces of the alkaline earth oxides or on rutile (110). There has been a high level of interest in studying the interaction of water and CO2 on alkaline earth metal oxide surfaces [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101] . The interaction of water at oxide surfaces is always of interest due to the presence of atmospheric water under many conditions and the possibility of surface hydroxylation.…”
Section: Introductionmentioning
confidence: 99%
“…Using small scale terracotta-MFC modules of roughly 10 cm height and 1 cm diameter in stacked systems, electricity was harvested from urine and other wastewaters to power DC motors and other devices (Walter et al, 2016). The same MFC design was utilized as a self-powered wastewater electrolyzer for electrocoagulation of heavy metals, caustic production at the cathode (pH > 10), and CO 2 sequestration (Ramírez-Moreno et al, 2014). Deposited salts and stripped ammonia can be thus recovered and utilized as fertilizers for agriculture in a circulareconomy approach [Behera et al, 2010;Sengupta et al, 2015].…”
Section: Introductionmentioning
confidence: 99%